Nurse‐led dexmedetomidine sedation for magnetic resonance imaging in children: a 6‐year quality improvement project. (28th January 2023) - Lin, R.; Lin, H.; Elder, E.; Cerullo, A.; Carrington, A.; Stuart, G.
Summary: We aimed to safely introduce dexmedetomidine into a nurse‐led sedation service for magnetic resonance imaging in children. Secondary aims were to increase the number of children eligible for sedation and to increase the actual number of children having sedation performed by our nurse sedation team. We analysed 1768 consecutive intravenous and 219 intranasal dexmedetomidine sedation episodes in infants, children and adolescents having magnetic resonance imaging scans between March 2016 and March 2022. The overall sedation success rate was 98.4%, with a 98.9% success rate for intravenous dexmedetomidine and a 95.0% success rate for intranasal dexmedetomidine. The incidence of scan interruption during intravenous and intranasal dexmedetomidine sedation was 8.8% and 21.9%, respectively. We conclude that paediatric sedation with dexmedetomidine for magnetic resonance scanning is safe and successful.